Contraceptive 3 Month Injection Booklet to Increase Knowledge and Attitude of The Acceptor - Putri, Rosalin Ariefah; Halimatussa'diah, Halimatussa'diah; Rahman, Gajali; Virawati, Dini Indo (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Contaceptive 3-month Injection Booklet is a type of printed media in book form to help health workers convey health messages. This research aims to determine the effect of using booklets on the knowledge and attitudes of 3-month contraceptive injection acceptors at Clinic, Samarinda. This research uses a quantitative type of research with a Quasi-Experimental research design (One Group Pre-post test design). The clarity was carried out in April-May 2024, with a population of 19 3-month contraceptive injection acceptors who visited the clinic. The sampling technique used accidental sampling due to the short research period and limited injectable contraceptive acceptors. data was obtained through pre-test and post-test questionnaires. The results of the analysis obtained a sig value of 0.002, where the p value is 0.05, which means that there is an influence of the use of booklets on the knowledge of 3-month contraceptive injection acceptors. It is determined that there is no impact of utilizing the booklet on the knowledge of 3-month injectable birth control acceptors since the sig value of 0.083 is more than >0.05 in contrast to the attitude value. The use of 3-month injectable contraceptive booklets is effective as a counseling tool to increase acceptor knowledge.